Finding Sarah : a duchess's journey to find herself - Ferguson, Sarah, Duchess of York, 1959- (Atria Books, 2011)
The author documents a low period in her life and how she found strength in her struggles with adversity and eventually regained her sense of purpose for her life with the help of friends and several celebrity experts.